The influence of valgus heel position on foot loading in a child's gait - Eliška Martinásková; Lucie Honzíková; Miroslav Janura; Zdeněk Svoboda (Palacky University, 2012)
BACKGROUND: Flat foot is a typical clinical sign in childhood, expressed as valgus positioning of the heel during vertical foot loading. This may lead to medial deviation of the foot axis and cause overloading of some foot areas. OBJECTIVE: To determine the influence of valgus position of the heel (both bilateral and unilateral) on foot loading during gait. METHODS: An experimental group consisting of children with bilateral heel valgus deformity (16 children, age 5.3 ± 1.3 years) and children with unilateral heel valgus deformity (14 children, age 5.6 ± 1.6 years). The control group comprised of 14 children (age 4.5 ± 1.2 years). For measuring foot loading during gait, the Footscan (RSScan International, Olen, Belgium) pressure plate was used. Each subject went through 8 trials of gait measurement. From each trial, 8 foot areas were evaluated. Data processing with mean values for each subject was performed by non-parametric tests (Mann-Whitney and Wilcoxon tests, Spearman correlation) in the STATISTICA programme (StatSoft, Inc., Tulsa, USA). RESULTS: Pressure peak and pressure impulse in the first metatarsal was greater for the bilateral valgus group (p < 0.01) in comparison to the control group. The group with unilateral valgus deformity showed greater pressure impulse in the medial heel (p < 0.05) and in the first (p < 0.01) and third metatarsal (p < 0.05) of the limb with non-valgus position of heel when compared to the limb with valgus heel position. Another significant difference (p < 0.01) between the valgus and non-valgus limb was found for the foot axis angle (non-valgus 8.2°, valgus 2.7°). CONCLUSION: The results show that valgus positioning of the heel influences foot loading in children during gait. The findings of this study suggest the necessity of a complex solution to the problem of preventing further progression of pathological changes.